Caffeoylquinic acids: chemistry, biosynthesis, occurrence, analytical challenges, and bioactivity. (23rd July 2021) - Alcázar Magaña, Armando; Kamimura, Naofumi; Soumyanath, Amala; Stevens, Jan F.; Maier, Claudia S.
SUMMARY: Caffeoylquinic acids (CQAs) are specialized plant metabolites we encounter in our daily life. Humans consume CQAs in mg‐to‐gram quantities through dietary consumption of plant products. CQAs are considered beneficial for human health, mainly due to their anti‐inflammatory and antioxidant properties. Recently, new biosynthetic pathways via a peroxidase‐type p ‐coumaric acid 3‐hydroxylase enzyme were discovered. More recently, a new GDSL lipase‐like enzyme able to transform monoCQAs into diCQA was identified in Ipomoea batatas . CQAs were recently linked to memory improvement; they seem to be strong indirect antioxidants via Nrf2 activation. However, there is a prevalent confusion in the designation and nomenclature of different CQA isomers. Such inconsistencies are critical and complicate bioactivity assessment since different isomers differ in bioactivity and potency. A detailed explanation regarding the origin of such confusion is provided, and a recommendation to unify nomenclature is suggested. Furthermore, for studies on CQA bioactivity, plant‐based laboratory animal diets contain CQAs, which makes it difficult to include proper control groups for comparison. Therefore, a synthetic diet free of CQAs is advised to avoid interferences since some CQAs may produce bioactivity even at nanomolar levels. Biotransformation of CQAs by gut microbiota, the discovery of new enzymatic biosynthetic and metabolic pathways, dietary assessment, and assessment of biological properties with potential for drug development are areas of active, ongoing research. This review is focused on the chemistry, biosynthesis, occurrence, analytical challenges, and bioactivity recently reported for mono‐, di‐, tri‐, and tetraCQAs. Significance Statement: Caffeoylquinic acids are specialized plant metabolites extraordinarily widespread in medicinal plants with interesting biological properties. This review is focused on the chemistry, biosynthesis, occurrence, analytical challenges, and bioactivity recently reported for mono‐, di‐, tri‐, and tetracaffeoylquinic acids.